Spectroscopy of a low global warming power refrigerant. Infrared and millimeter-wave spectra of trifluoroethene (HFO-1123) in the ground and some vibrational excited states. (June 2020) - Tamassia, Filippo; Melosso, Mattia; Dore, Luca; Pettini, Michele; Canè, Elisabetta; Stoppa, Paolo; Pietropolli Charmet, Andrea
Highlights: Analysis of the infrared band ν 6 . Rotational spectra in the ground and vibrational excited states. FT-IR detection of many fundamental bands. Abstract: In the present work we carried out a combined rotational and ro-vibrational investigation on 1, 1, 2-trifluoroethene, a relevant unsaturated hydrofluoroolefin recently proposed as refrigerant in mixture with other halogenated compounds (like difluoromethane). By employing a frequency-modulation millimeter-wave spectrometer, the rotational spectra were recorded in the frequency ranges 80–96 GHz and 245–260 GHz for the ground and also the vibrationally excited states ν 8 = 1, ν 9 = 1, ν 12 = 1, ν 9 = 2, ν 12 = 2, and ν 9 = ν 12 = 1 . In addition, the infrared spectra in the region of the ν 6 band (centered at 929.8 cm − 1 ) were measured with a high-resolution Fourier transform spectrometer. The data coming from the detailed rotational and ro-vibrational assignments were combined in a global fit, taking into account also the ground state transitions available in the literature. From this analysis, a very accurate set of rotational and centrifugal distortion constants was determined for the ground state and for all the vibrationally excited states here investigated.